Identifying Shahid Sattari’s Strategic Leadership Competencies: Teachings for Public Managers - Naser Asgari (مدیریت دولتی)
Objective In today’s complex and dynamic organizational environments, strategic leaders play a pivotal role in shaping strategies, driving transformational initiatives, achieving organizational excellence, and ensuring long-term survival and success. These responsibilities demand a diverse set of competencies that enable leaders to navigate challenges and seize opportunities effectively. Understanding and developing these competencies is crucial for fostering strategic leadership. The present study seeks to identify the strategic leadership competencies (SLC) of Shahid Mansour Sattari, a prominent strategic leader, and to design a comprehensive model based on his demonstrated capabilities and achievements. By exploring Sattari's leadership competencies, this study aims to contribute to the development of strategic leaders and provide actionable insights for organizations. Methods This research adopts an applied, interpretive, and inductive approach within a qualitative framework. The data sources include Shahid Sattari’s recorded and documented memories, published books and articles about him, cinematic portrayals of his life, and the Sattari database. These materials were purposefully selected and analyzed using thematic analysis. To ensure reliability, the two-coder agreement method was employed to evaluate and confirm findings. Additionally, expert opinions were solicited to validate the identified categories, and necessary adjustments were incorporated. This rigorous methodological approach ensures the credibility and applicability of the study's findings.